Learning and earning. (Economist, 2017)
The article discusses the need for continuing education and worker retraining due to economic conditions as of 2017. Topics include the success of the computer programming education firm General Assembly, the relation between wages and educational attainment in the U.S., and the impact of automation on employment levels.